Understanding Mathematics Learning Difficulties in Elementary Education: An Analysis of Contributing Factors and Teacher Intervention Strategies - Meilin Arnia Nur Azizah; Asrul Asrul; Lina Kumalasari (Papanda Publisher, 2026)
Mathematics learning difficulties significantly impede elementary students' academic development, yet limited research examines practical intervention strategies for resource-constrained rural contexts. This qualitative descriptive study investigated factors contributing to mathematics learning difficulties among third-grade students at Muhammadiyah Rawa Sugih Elementary School, Indonesia. Data were collected through semi-structured interviews with one classroom teacher and one principal, supplemented by systematic classroom observations over one month (eight sessions). Analysis followed Miles and Huberman's interactive model, with source triangulation ensuring validity. Students exhibited three primary difficulty categories: conceptual understanding of multiplication/division, procedural computational fluency, and word problem comprehension. Internal factors—low motivation, minimal interest, and negative attitudes—dominated as primary contributors, reinforced by external factors including limited parental support, disruptive peer influences, and inadequate instructional resources. Teacher intervention strategies combining individual guidance, systematic material repetition, mobile phone-based audio-visual media, and WhatsApp-mediated parent communication demonstrated modest effectiveness in enhancing student engagement and homework completion rates (40% to 75%). Findings support ecological-transactional models wherein learning difficulties emerge from dynamic interactions between individual characteristics and environmental conditions rather than solely individual deficits. The integration of accessible digital communication platforms represents a scalable innovation for strengthening home-school partnerships in resource-limited settings, extending theoretical understanding of technology-mediated parental involvement in elementary mathematics education.